Advancing Pharm. D. Training in Egypt through a Structured Preceptor Development Program - Toral C. Patel; Jodie V. Malhotra; Joseph J. Saseen (MDPI AG, 2020)
The Children's Cancer Hospital of Egypt (CCHE) and the University of Colorado Skaggs School of Pharmacy and Pharmaceutical Sciences (SSPPS) collaborate to offer a Doctor of Pharmacy (Pharm.D.) degree to international pharmacists holding a bachelor's degree in pharmacy. The experiential training is provided by CCHE's clinical pharmacist preceptors at CCHE. Clinical pharmacists at CCHE had prior experience precepting baccalaureate pharmacy students, but not Pharm.D. students when this program commenced. Therefore, the SSPPS faculty provided a live preceptor development program for select CCHE clinical pharmacists in 2017. Primary deliverables of the program included the preparation of individual preceptor development plans and experiential syllabi for program participants. Preceptor development plans and experiential syllabi were evaluated by the SSPPS faculty. Program participants were also evaluated on their assessment of learner case scenarios using introductory pharmacy practice experience (IPPE) and advanced pharmacy practice experience (APPE) assessment tools created for the CCHE program. Participant performance on submitted preceptor development plans and experiential syllabi, and performance on the learner cases were all utilized for participant selection as Pharm.D. preceptors in the CCHE Pharm.D. program. This paper describes this preceptor development program, the process utilized to determine selection of Pharm.D. preceptors, and plans for providing continuing preceptor development for preceptors at CCHE.